Outcomes and Predictors of Toxicity after Selective Internal Radiation Therapy Using Yttrium-90 Resin Microspheres for Unresectable Hepatocellular Carcinoma - Gabrielson, Andrew; Miller, Akemi; Banovac, Filip; Kim, Alexander; He, Aiwu Ruth; Unger, Keith (Frontiers in Oncology, 2015)
Purpose We sought to report outcomes and toxicity in patients with hepatocellular carcinoma (HCC) who received resin yttrium-90 selective internal radiation therapy (90Y-SIRT) and to identify factors associated with declining liver function. Methods Patients treated with 90Y-SIRT were retrospectively evaluated. Radiographic response was assessed using RECIST 1.1. Median liver progression-free survival (LPFS) and overall survival (OS) were calculated using the Kaplan–Meier method. Bivariate analysis was used to examine associations between change in Child-Pugh (CP) score/class and patient characteristics and treatment parameters. Results Twenty-seven patients with unresectable HCC underwent SIRT, 52% were CP Class A, 48% were Class B, 11% were BCLC stage B, and 89% were stage C. Forty-four percent of patients had portal vein thrombus at baseline. One-third of patients received bilobar treatment. Median activity was 32.1 mCi (range 9.18–43.25) and median-absorbed dose to the liver was 39.6 Gy (range 13.54–67.70). Median LPFS and OS were 2.5 and 11.7 months, respectively. Three-month disease control rate was 63 and 52% in the target lesions and whole liver, respectively. New onset or worsened from baseline clinical toxicities were confined to Grade 1–2 events. However, new or worsened Grade 3–4 laboratory toxicities occurred in 38% of patients at 3 months and 43% of patients at 6 months following SIRT (six had lymphocytopenia, three had hypoalbuminemia, and two had transaminasemia). After 3 months, six patients had worsened in CP score and five had worsened in class from baseline. After 6 months, four patients had worsened in CP score and one had worsened in class from baseline. Pretreatment bilirubinemia was associated with a 2+ increase in CP score within 3 months (P = 0.001) and 6 months (P = 0.039) of 90Y-SIRT. Pretreatment transaminasemia and bilirubinemia were associated with increased CP class within 3 months of SIRT (P = 0.021 and 0.009, respectively). Conclusion 90Y-SIRT was well-tolerated in patients with unresectable HCC, with no Grade 3–4 clinical toxicities. However, Grade 3–4 laboratory toxicities and worsened CP scores were more frequent. HCC patients with pretreatment bilirubinemia or transaminasemia may be at higher risk of experiencing a decline in liver function following 90Y-SIRT.